Investigation on Antimicrobial Resistance Levels of Escherichia coli Strains Isolated from Bovine Fecal Samples and Comparison with Guidelines of the Clinical Laboratory Standards Institute (CLSI) and European Committee on Antimicrobial Susceptibility Testing (EUCAST) - Kalın, Recep; Karagülle, Burcu; Acik, Mehmet Nuri; Karahan, Murat; Öztürk, Yasin; Cetınkaya, Burhan (My University, 2023)
This study was carried out to investigate the antibiotic resistance levels of Escherichia coli isolates of bovine origin and to compare the results with CLSI and EUCAST guideline values. For this purpose, 97 E. coli strains isolated from fecal samples of cattle in 12 different farms were tested against 32 antibiotics by using the disk diffusion method. The zone diameters of 13 antibiotics examined within the scope of the study were compared according to the CLSI and EUCAST 2020 guidelines, and their consistency levels were evaluated statistically. The highest resistance rates in E. coli isolates were determined against tetracycline (68%), streptomycin (63.9%), ampicillin (58.8%), and doxycycline (50.5%) antibiotics. On the other hand, the isolates were found to be highly susceptible to amikacin and cephalosporin group antibiotics. When CLSI and EUCAST guidelines were compared, it was found that there were statistically significant differences between the resistance rates of nitrofurantoin, gentamicin, and amikacin. Only 10 (10.3%) of the isolates were detected to be susceptible to all the antibiotics tested, whereas 17.5% were resistant to 10 or more antibiotics. The results of this study showed that E. coli isolates of bovine origin were highly resistant against antibiotics used in the field for a long period, especially the number of isolates with multiple antibiotic resistance was striking. It was concluded that due to substantial inconsistencies between the CLSI and EUCAST guidelines for some antibiotics such as amikacin, nitrofurantoin, and gentamicin, there is an urgent need to execute necessary updates in both guidelines.
Keywords: Escherichia coli; Bovine; Antibiotic resistance; CLSI; EUCAST